Penggunaan Alat Peraga Matematika Untuk Meningkatkan Motivasi Belajar Siswa Kelas 5A di MIS Nahdlatul Ulama - Muhamad Ridho; Istiyati Mahmudah (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The purpose of this research was to find out how many benefits and how high the value of teaching aids, especially mathematics teaching aids, used by a mathematics teacher during learning to increase the learning motivation of VA MIS class students. Nahdlatul Ulama Palangkaraya. The method used by researchers during the research was the interview method and direct observation of the research object, which consisted of teachers, students, learning approaches and teaching aids used in mathematics learning. It is hoped that after the research, readers and researchers as prospective teachers will realize how important the use of teaching aids, especially mathematics teaching aids, is in increasing students' learning motivation in class. And through this research, researchers also show that students are motivated to learn mathematics compared to learning without using teaching aids, students tend to show a passive attitude and are not enthusiastic when learning takes place.